Fallibilism and the flexibility of epistemic modals - Anderson, C (2014)
It is widely acknowledged that epistemic modals admit of inter-subjective flexibility. This paper introduces intra-subjective flexibility for epistemic modals and draws on this flexibility to argue that fallibilism is consistent with the standard account of epistemic modals. © 2013 Springer Science+Business Media Dordrecht.